Influência da avaliação neurológica seriada e seus reflexos no prognóstico funcional de recém-nascidos a termo com asfixia perinatal - Freitas, Záira Moura da Paixão (2016)
Background: According to the World Health Organization, between four to nine million newborns develop birth asphyxia. It is estimated that 1.2 million fatal outcomes and at least the same number develop disabling neurological sequelae and developmental delay. Early neurological evaluation promotes the improvement of the life expectancy of serious asphyxiated babies and It can be incorporated into the routine of neonatal intensive care units. Glasgow Coma Scale adapted for children can be an assessment tool used in high-risk newborns. Objective: To compare the clinical outcome of term infants with perinatal asphyxia (PA) moderate and severe that underwent a neurological neonatal serial evaluation protocol during hospital stay, with those not undergoing evaluation. Method: This is an epidemiologic, observational and analytical study, using a quantitative approach. The study considered two groups, intervention and control. For the control group, at first, it was made a survey data in charts and then the longitudinal, prospective, observational approach was adopted during the period of outpatient care. For the intervention group, a longitudinal approach, prospective, observational was used during the hospital stay and follow-up clinic. We sought to investigate the neurological clinical course of children, the length of stay in hospital and delay presence in the development of neuromotor skills. Results: The sample consisted of 112 newborns, 86 infants in the control group and 26 infants in the intervention group. The intervention group showed a median of less hospital stay (p<0.001) than the control group. Full-term newborns diagnosed with PA, which remained for a shortest time in hospital length and were subjected to a serial neurological evaluation protocol, incorporated into standard clinical procedures in the NICU for the management of PA, did not show disturbances in neuromotor development. Conclusion: The use of serial neurological evaluation protocol influenced significantly, the prevalence of delayed neuromotor development.